Character Building As An Academic Foundation Towards An Excellent Islamic Senior High School - Setiawan, Aan; Badaruddin, Sukri; Hasanuddin, Muhammad Idris; Arsalan, Muammar Zuhdi; Al-Muthmainnah, Al-Muthmainnah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze character building among students through intracurricular activities at Madrasah Aliyah Darud Da’wah Wal Irsyad (MA DDI) Baruga. The research focuses on the role of teachers in classroom learning, the teaching methods applied, and the strategies used to internalize character values within intracurricular activities. This research employs a qualitative approach, in which the researcher directly visited the field to conduct observations, interviews, and document analysis. The primary data sources are the principal and teachers who are directly involved in implementing intracurricular activities. Data were analyzed using the NVIVO application through several stages, namely open coding, axial coding, and visualization. The findings indicate that character building in intracurricular activities is manifested primarily in biology and mathematics classes through project-based learning models. The character values internalized include integrity, independence, cooperation, and religiosity. The process of internalization is not carried out rigidly or dogmatically but through dialogic learning that stimulates students’ moral and spiritual awareness. This approach aligns with the moral knowing dimension of Lickona’s character education theory, emphasizing cognitive understanding accompanied by reflection on values. It also resonates with the Mandar cultural value of malaqbiq, which upholds manners and honor as a noble social identity. Thus, the learning process at MA DDI Baruga serves not only as a medium for knowledge transfer but also as an effort to shape students’ character rooted in Islamic teachings, modern educational theory, and local wisdom.